The Indonesianization of Social Medicine - Vivek Neelakantan (Universitas Gadjah Mada, 2013)
The purpose of social medicine, which began in Europe as an academic discipline during the Second World War, was to investigate the correlation between specifc factors such as age, gender, race, heredity, economic circumstances, domestic environment, occupation and nutrition on health. Almost a decade later, Indonesian physicians applied social medicine ideas to promote public health in a country characterized by weak state intervention. These physicians eschewed the narrow correlation between poverty and ill health but reinterpreted social medicine within the Indonesian social context with its entrenched patriarchal system and cultural preferences. The wider theme explored in this article concerns the emergence of social medicine in twentieth-century Indonesia as a critical reaction to Dutch public health policies. The article examines the partnership between Indonesian physicians and the post-colonial state and their shared vision on state-guided social medicine, but does not explore why social medicine failed to usher in a transformation of the nation’s health system.